Combined effect of type and capture area of counting chamber and diluent on Holstein bull sperm kinematics. (27th December 2018) - Valverde, Anthony; Areán, Hector; Fernández, Alejandro; Bompart, Daznia; García‐Molina, Almudena; López‐Viana, Javier; Soler, Carles
Abstract: The evaluation of sperm motion is crucial for processing of seminal doses for artificial insemination. Here, the combined effect of the type and capture area of three counting chambers, together with the type of diluent employed, on sperm motility was analysed. Ejaculates from thirteen Holstein bulls were used for sperm kinematic analysis with the ISAS ® v1 CASA‐Mot system, using two capillary‐loaded counting chambers (Leja ® and Cell‐Vu ® ) and one drop displacement chamber (Makler ® ). Nine fixed positions were analysed per chamber type, considering central and lateral and three longitudinal fields. Independent of the diluent used, differences were found between the three chambers. Independent of the extender, no differences in x‐axis were observed with Cell‐Vu ®, while using Leja ®, some parameters showed lower values in the centre than in lateral areas. In both counting chambers, the lowest values were observed in the distal area. Results obtained with the two diluents were highly different with a very low correlation between them. In conclusion, the capture area inside the chambers leads to significant changes in sperm kinematic parameters and different dilution media introduce considerable differences in the motility patterns. It is necessary to optimise sampling methods and specific set‐ups to be used with CASA‐Mot technology.